Field-induced partial disorder in a Shastry-Sutherland lattice - Madalynn Marshall; Brianna R. Billingsley; Xiaojian Bai; Qianli Ma; Tai Kong; Huibo Cao (Nature Communications, 2023)
Abstract A 2-Q antiferromagnetic order of the ferromagnetic dimers was found below T N = 2.9 K in the Shastry-Sutherland lattice BaNd2ZnS5 by single crystal neutron diffraction. The magnetic order can be understood by the orthogonal arrangement of local Ising Nd spins, identified by polarized neutrons. A field was applied along [1 -1 0] to probe the observed metamagnetic transition in the magnetization measurement. The field decouples two magnetic sublattices corresponding to the propagation vectors q 1  = (½, ½, 0) and q 2  = (−½, ½, 0), respectively. Each sublattice shows a “stripe” order with a Néel-type arrangement in each single layer. The “stripe” order with q 1 remains nearly intact up to 6 T, while the other one with q 2 is suppressed at a critical field H c ~1.7 T, indicating a partial disorder. The H c varies with temperature and is manifested in the H-T phase diagram constructed by measuring the magnetization in BaNd2ZnS5.